PENGEMBANGAN MEREK DAN PENGKAJIAN STRATEGI PEMASARAN DI DEPOT RASA SUKA KEDIRI - Rini Raharjo; Rosita Meitha Surjani; Esti Dwi Rinawiyanti (Perpustakaan Universitas Surabaya, 2013)
Depot Rasa Suka is a culinary business that provides a variety of Indonesian dishes. However people still do not know and yet loyal to Depot Rasa Suka due to the unavailability of parking space, quite a long serving time, hot room, less attractive promotion and room design. Therefore Depot Rasa Suka need to devise strategies to develop brands through brand equity analysis and improvement of brand elements as well as designing a marketing strategies. The goal of this research is to make Depot Rasa Suka has a strong brand image and could meet the desires of consumers based on consumer behavior to ensure that customers remain loyal and increase sales in Depot Rasa Suka. The research was conducted by distributing questionnaire to the group of respondents that consists of actual consumers and potential consumers. Based on the measurement of brand equity, brand equity scores for Depot Rasa Suka is 2 (medium). In order to enhance the brand equity it is necessary to develop brand elements such as brand names or logos, packaging, website, and marketing communications activities. Segmentation for Depot Rasa Suka is determined based on consumer behavior analysis including demographics (age, marital status, education level, occupation, and income) and psychographics (knowledge, attitude, uses, occasions, benefits sought, usage rate, and loyalty status). The target market is aged 20-30 years old, self-employed occupations, average earnings per month Rp 3,000,000.00 - 6,000,000.00 and spending per visit to the restaurant Rp 50,000.00 - 100,000.00. The positioning of Depot Rasa Suka is positioning according to quality and price. The differentiation of Depot Rasa Suka is product differentiation. Total cost in the proposed strategy is Rp 10,511,000.00.